2020
DOI: 10.3390/polym12092107
|View full text |Cite
|
Sign up to set email alerts
|

Basalt Fiber Modified Ethylene Vinyl Acetate/Magnesium Hydroxide Composites with Balanced Flame Retardancy and Improved Mechanical Properties

Abstract: In this study, we selected basalt fiber (BF) as a functional filler to improve the mechanical properties of ethylene vinyl acetate (EVA)-based flame retardant materials. Firstly, BF was modified by grafting γ-aminopropyl triethoxysilane (KH550). Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscope (SEM), and energy dispersive X-ray spectroscopy (EDS) were used to comprehensively prove the successful modification of the BF surface. Subsequently, the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Before the basalt fiber was modified formally by silane, pretreatment to the fiber was carried out in this study in order to clean the surface. By referring to the previous studies [ 20 , 21 , 22 , 23 ], four different pretreatment approaches were used to basalt fibers: 10 g basalt fibers were immersed in 200 mL acetone solution ultrasonic cleaning at 50 °C for 3 h, then the fibers were soaked in acetone for 21 h and dried for 48 h at 60 °C after the filtration. 10 g basalt fibers were immersed in 150 mL glacial acetic acid ultrasonic and cleaned at 50 °C for 3 h using sonication bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the basalt fiber was modified formally by silane, pretreatment to the fiber was carried out in this study in order to clean the surface. By referring to the previous studies [ 20 , 21 , 22 , 23 ], four different pretreatment approaches were used to basalt fibers: 10 g basalt fibers were immersed in 200 mL acetone solution ultrasonic cleaning at 50 °C for 3 h, then the fibers were soaked in acetone for 21 h and dried for 48 h at 60 °C after the filtration. 10 g basalt fibers were immersed in 150 mL glacial acetic acid ultrasonic and cleaned at 50 °C for 3 h using sonication bath.…”
Section: Methodsmentioning
confidence: 99%
“…Before the basalt fiber was modified formally by silane, pretreatment to the fiber was carried out in this study in order to clean the surface. By referring to the previous studies [20][21][22][23], four different pretreatment approaches were used to basalt fibers:…”
Section: Preparation Of Modified Basalt Fibersmentioning
confidence: 99%
“…Various studies are available in literature in which they suggested investigation on several inorganic materials to be applied as filler [77,78,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] in a polymer and in some used both fibers and inorganic fillers combined. [123][124][125][126][127] In reference to this, mechanical properties such as Young's modulus, tensile strength, impact strength, and flexural strength of polymer composites filled with unmodified and/or modified magnesium hydroxide are reviewed. Furthermore, a summary of mechanical properties investigated in the literature is shown in Table 6.…”
Section: Mechanical Properties Of Magnesium Hydroxide/polymer Compositesmentioning
confidence: 99%
“…Conversely, the noncovalent modification conditions of organic polymer coatings is mild, making it an ideal modification method [ 21 , 22 , 23 ]. In addition, previous research has shown that inorganic nanomaterials modified with organic polymers may improve the compatibility and interface interaction between the nanoparticles and the matrices, allowing them to achieve better performance, as compared to that of other common composite materials [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%